Impact of Plasmapheresis on the Time Course of Changes in Cytokines After Operations on the Heart and Great Vessels - A. A. Yeremenko; A. A. Ragimov; S. A. Poreshina; M. A. Babayev; L. I. Vinnitsky; I. N. Solovyeva (Общая реаниматология, 2005)
Objective. To assess the impact of plasmapheresis on the time course of changes in pro- and anti-inflammatory interleukins and the results of treatment in patients after complicated operations on the heart and great vessels.Material and methods. 44 patients were examined. In 33 patients, the intra- and postoperative period was complicated by a prolonged extracorporeal circulation (EC), massive blood loss, acute hemolysis, the development of disseminated intravascular coagulation. The above complications gave grounds to perform plasmapheresis (PA) in different postoperative periods. The patients were equally divided into 4 groups (each containing 11 patients): 1) patients with multiple organ dysfunction (MOD), in whom PA was conducted within 2—6 hours after surgery; 2) those without MOD, in whom PA was also performed within 2—6 hours after surgery; 3) those with MOD in whom PA was made 16-20 hours after surgery; 4) a control group (receiving no PA), the early postoperative period was normal. Interleukins (IL) 6, 8, and 10 and the oxygenation index (OI) after surgery and in the first 24 postoperative hours, the duration of EC, the volume of blood loss, and a postoperative clinical period were studied.Results. The duration of EC was highest in Group 1 patients and 37 and 130% greater in Groups 2 and 3, respectively. The elevated levels of IL-6 were noted in all the patients. In the early post-PA periods, the content of IL-6 was decreased by 30% in Groups 1 and 2 patients. In Group 3, the level of IL-6 remained unchanged within the first 24 hours. The postoperative concentration of IL-8 was increased in all the patients. There were no changes in the content of IL-8 after surgery and within the first 12 hours. In Group 3 patients, the level of IL-8 within the first 24 hours was 5 times higher than that observed just after surgery. In patients with developed MOD, a correlation was found between IL-8 and OI postoperatively and within the first 24 hours after surgery. The level of IL-10 was higher in patients without developed MOD. Groups 1, 2, and 4 showed a significant decrease in the concentration of IL-10 by the first 24 postoperative hours as compared with the baseline values. The content of LI-10 remained unchanged in Group 3 patients.Conclusion. A systemic inflammatory response accompanied by the elevated levels of pro- and anti-inflammatory IL develops in all the patients undergoing surgery under EC. The subsequent development of MOD is determined by the imbalance between the alternative pools of cytokines. The correlation between the levels of IL-8 and OI suggests that this cytokine plays an important role in the development of postoperative respiratory failure. Indications for the use of PA are high risk factors of MOD (blood loss, more than 26 ml/kg; the duration of EC, more than 165 min). PA performed in early postoperative periods prevents the development of MOD and reduces mortality rates up to 2%. With subsequent progression of MOD, the mortality rates are 28 and 42% with early and late PA, respectively.